1985
DOI: 10.1111/j.1399-0004.1985.tb00402.x
|View full text |Cite
|
Sign up to set email alerts
|

Variable clinical presentation of cutis laxa

Abstract: We present 2 families with 4 individuals suffering from congenital cutis laxa. Family A has a single affected male child with developmental delay and ligamentous laxity, making this only the second male of the total 15 patients so far reported with this particular syndrome. Family B has 3 affected males, 2 of whom have significant involvement of other systems. Only one of the 4 affected children had very obvious loose skin folds and dependency on this clinical feature alone could result in under‐diagnosis of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
0

Year Published

1997
1997
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(10 citation statements)
references
References 7 publications
2
6
0
Order By: Relevance
“…Accordingly, in adult patients with normal nutritional status skin wrinkling and the general appearance was not striking enough to suspect a genetic syndrome. Similar observations were made previously [Gazit et al, 1973;Fitzsimmons et al, 1985]. Hunter [1988] suggested that GO may be underdiagnosed, which may be also be true for WSS.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…Accordingly, in adult patients with normal nutritional status skin wrinkling and the general appearance was not striking enough to suspect a genetic syndrome. Similar observations were made previously [Gazit et al, 1973;Fitzsimmons et al, 1985]. Hunter [1988] suggested that GO may be underdiagnosed, which may be also be true for WSS.…”
Section: Discussionsupporting
confidence: 80%
“…This phenotype tends to regress with age and the improvement of the nutritional status (Fig. 4) similar to previous descriptions [Fitzsimmons et al, 1985;Patton et al, 1987]. Not all of our WSS infants were malnourished and we expect the diagnosis of WSS may be overlooked in the absence of malnutrition.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Cutis laxa is a rare connective tissue disorder, which may be inherited or acquired, and is characterized by progressive looseness of skin, associated with abnormalities of other organs and structures such as lung, vasculature or gastrointestinal tract[1] as they contain elastic tissues. The hereditary form of cutis laxa may be inherited as either autosomal dominant, X-linked recessive or autosomal recessive trait.…”
Section: Introductionmentioning
confidence: 99%
“…[46] The clinical appearance is characterized by inelastic, loose and pendulous skin that produces a wrinkled, prematurely aged appearance. [1] The primary change is in the elastic fiber, which is decreased or nearly absent in the dermis. [7] Here, we describe 2 cases of acquired cutis laxa.…”
Section: Introductionmentioning
confidence: 99%